O uso do reconhecimento fotográfico como meio de prova e a incidência de falsas memórias - Machado, Ângela Prandi (2024)
The present study seeks to analyze the use of photographic recognition to obtain evidence and the consequences that the incidence of false memories can cause for the procedural outcome and even for possible conviction of the individual being investigated in a given criminal case. In that regard, it is necessary to discuss the evolution of the production of evidence in the criminal sphere, as well as understand how human memories are formed, taking into account all the elements that can influence the report of the witness or victim, so that the evidence collected is, above all, free from defects or propensities for a given person. This is how it becomes visibly necessary to analyze the possible occurrence of false memories and their influence on the criminal process, especially when it comes to authorship criminal.